Dipping Pattern and 1-year stroke functional outcome in ischemic stroke or transient ischemic attack. (31st December 2023) - Ding, Xia; Zhou, Yilun; Pan, Yuesong; Xu, Jie; Yan, Hongyi; Zhao, Xingquan; Wang, Yilong; Wang, Yongjun
ABSTRACT: Aims: This study aimed to explore whether a relationship exists between dipping patterns and 1-year functional outcome in patients with acute ischemic stroke (IS) or transient ischemic attack (TIA). Methods: Data from the Blood Pressure and Clinical Outcome in TIA or Ischemic Stroke Study (BOSS), a nationwide, hospital-based, longitudinal cohort study, was used for this study. Patients with acute IS or TIA were recruited within 7 days after onset and ambulatory blood pressure monitoring was performed during hospitalization. Patients were defined as dippers if nocturnal systolic blood pressure fell by ≥10%, non-dippers if 0–10%, and reverse dippers if < 0%. Poor functional outcome was defined as a modified Rankin Scale (mRS) score of 3–5. Logistic regression analysis was used to test the association between dipping patterns and 1-year functional outcome. Results: Among the 1808 IS/TIA patients, 19.19% were dippers, 53.21% were non-dippers, and 27.60% were reverse dippers. Poor functional outcome occurred in 22.44% of reverse dippers, which was significantly higher than that of dippers (16.14%) and non-dippers (16.53%) (P = .014). A univariate analysis revealed that reverse dipping was a risk factor for poor functional outcome (Odds ratio 1.504, 95% confidence interval 1.055–2.145, P = .024). However, this significance disappeared after adjusting for confounders. Conclusions: Reverse dipping was prevalent in patients with IS/TIA. The higher incidence of 1-year poor functional outcome in reverse dippers warrants further investigation.